The potential of augmented reality books to influence reading attitudes of 8-9 year old children : an exploratory study - Agorou, Antonia; Kallinikou, Emily; Kyriacou, Evdoxia; Miltiadous, Konstantina; Nicolaidou, Iolie (My University, 2018)
Augmented reality (AR) is a fast growing field in entertainment, and more recently in education. Augmented reality books merge traditional text with digital content using technologies such as a smartphone or tablet combined with the use of an app which plays video, and allows for interaction with the text. AR books show potential for creating a more motivating and engaging reading experience, especially for young, struggling readers. But to what extend can AR books affect young children’s reading attitudes? Recent research focused on AR books in relation to reading skills, cognitive load, motivation, and attitudes, and children's and parents' behavioral patterns. A research gap was identified in relation to the examination of the potential effect of AR on the reading attitudes and habits of young children. This exploratory case-study attempted to address this gap. Participants included 30 children (16 boys, 14 girls) aged 8-9 years old, with no prior experience with AR, selected through convenience sampling. Children first completed a reading attitudes questionnaire, of 5 statements in 10-point likert-scale. They then individually interacted with an AR book about “the world’s famous landmarks” and a tablet or smart-phone. A researcher completed fieldnotes. Children finally completed a “reading attitudes in relation to AR books questionnaire”, of 8 statements in 10-point likert-scale. Results of the quantitative data analysis showed that prior to the AR experience, children in general had positive attitudes towards reading (M=8.35 out of 10, SD=1.63, N=30) and considered themselves good in reading (M=8.27, SD=2.43, N=30). Approximately one in three children reported that they read books daily (33.3%, 10/30), often (30%, 9/30) or sometimes (36.7%, 11/30). After their first reading experience of an AR book, children in general had positive attitudes towards AR (M=8.11, SD=1.09, N=30). More specifically, they liked reading an AR book (M=8.97, SD=1.52) and enjoyed using the tablet while reading the AR book (M=9.53, SD=1.38) at a great extent. They also reported that they would read books more often if those books were AR books (M=9, SD=1.66). Nine-year-old children indicated a statistically significant (t=-2.15, DF=28, p=0.04) stronger preference towards obtaining an AR book (M=8.5, SD=2.06) compared to 8-year-olds (M=6.6, SD=2.82). The qualitative data analysis of field notes resulted in the classification of children in four types of readers: a) enthusiastic with reading but not with AR (40%, 12/30), b) enthusiastic with AR but not with reading (33.3%, 10/30), c) enthusiastic with both AR and reading (23.3%, 7/30), and d) showing no interest in reading nor AR (3.3%, 1/30). The quantitative data analysis of this study provided a strong indication that 8-9-year-old children who already have positive attitudes towards reading, enjoy reading an AR book. Children also claim that they would read books more often if those were AR books. However, qualitative data analysis revealed that an important percentage of children (40%, 12/30) seem to prefer “traditional reading” compared to “reading enhanced with the AR experience”. Future studies that will examine the connection between AR and reading attitudes in young children should be longitudinal and focus specifically on struggling readers or children with negative attitudes towards reading.
Keywords: reading; attitudes; young children; augmented reality (AR)